Preliminary design of lower power gained solar energy system in Malaysia / Mohd Norazlisham Mohd Ali. - Mohd Ali, Mohd Norazlisham (2009)
Humankind is facing a great global environmental problems. The factor of the problems are caused primarily by massive consumption of fossil fuels such as coal and oil. The key to resolving these problems lies in the development of clean energies. Solar cells are the key technology toward the conquest of global environmental problems which convert sun-light directly into electricity. In this aspect of safety and availability, solar energy is the ideal form of energy because it is clean, inexhaustible, and approximately 95% parts of the world. A solar photovoltaic (PV) represents a very important part of the technology revo-lution in the last few decades. With application solar photovoltaic on the satellites, hu-mankind can communicate to each other. The application of solar photovoltaic (PV) is not widely used in Malaysia even there is a need in the rural areas where no electricity is available. The objectives of this project to study and design of lower gained solar system in Malaysia for small office or house (less than l0kW). Besides, detail explanation about how conversion from solar energy into energy generation, consideration about related components solar system development at Malaysia. Several of preliminary design has been develop with respect to the required output and input. The signification of these results of this paper will be used for future understanding about solar energy system. In orders words, the results can gives some ideas contribution to solar energy system in Malaysia. The re-sults of research to give preliminary design of lower gained solar energy system in Malay-sia. Besides, the results can give information about the best material can used, method for solar energy system and input parameter for system.